Innocent until interrogated the true story of the Buddhist Temple Massacre and the Tucson Four - Stuart, Gary L., 1939-; ebrary, Inc. (Tucson : University of Arizona Press, 2010)
Recounts the events surrounding the murders of nine Buddhist temple members near Phoenix, Arizona, and the arrest of four men known as "The Tucson Four" who were coerced into confessing and held despite there being no physical evidence to connect them to the crime, and discusses how the suspects were treated by the media, even after the real killers were discovered.
A circle of death -- The sheriff's task force -- The man with many names -- A waiting line for confessions -- Recantations and indictments -- The forgotten murder weapon -- Political wrangling -- A murderer ten times over -- Johnathan Doody on trial -- Mitigation, aggravation, and sentencing -- Suing Maricopa County.
Includes bibliographical references (p. [301]-330) and index.
Electronic reproduction.
Keywords: Murder -- Investigation -- Arizona -- Maricopa County; Judicial error -- Arizona; Electronic books